Strengthening digital capacity and disaster safety for the Merapi slope tourism jeep community - Prawoto, Nano; Nurjanah, Adhianty; Damarjati, Cahya (Community Empowerment, 2025)
The Merapi slopes area in Sleman is a disaster-prone region that also serves as a potential destination for jeep tourism. The main challenges faced are a lack of digital promotion capacity and disaster preparedness. This community service aimed to enhance the economic independence and safety of the Merapi Jeep Community by strengthening digital promotion, implementing a Disaster Response Information System (SIMANTAB), and developing Safe Tourism SOPs. The implementation methods included socialization, training, technology application, and mentoring. Interventions encompassed digital marketing training, SIMANTAB integration, SOP development, and fulfillment of safety standards (SNI helmets). The program results showed a significant increase in partner understanding (averaging over 80%) in disaster mitigation and digital marketing aspects, as well as 88% success in developing Safe Tourism SOPs. This program impacted professionalism, tourist trust, and income potential. Program sustainability is ensured through the formation of a local master trainer team, establishing an effective collaborative model for sustainable tourism in disaster-prone areas.